Applying the Behavior Change Technique Taxonomy to Four Multicomponent Childhood Obesity Interventions. (May 2021) - JaKa, Meghan M.; Wood, Caroline; Veblen-Mortenson, Sara; Moore, Shirley M.; Matheson, Donna; Stevens, June; Atkins, Lou; Michie, Susan; Adegbite-Adeniyi, Clara; Olayinka, Oluwatomisin; Po'e, Eli K.; Kelly, Alethea M.; et al.
Applying the Behavior Change Technique Taxonomy has the potential to facilitate identification of effective childhood obesity intervention components. This article evaluates the feasibility of coding Childhood Obesity Prevention and Treatment Consortium interventions and compares reliability between external taxonomy-familiar coders and internal intervention-familiar coders. After training, coder pairs independently coded prespecified portions of intervention materials. An adjudication process was used to explore coding discrepancies. Reliability between internal and external coders was moderate (prevalence and bias-adjusted kappa .38 to .55). Reliability for specific target behaviors varied with substantial agreement for physical activity (.63 to .76) and moderate for dietary intake (.44 to .63). Applying the taxonomy to these interventions was feasible, but agreement was modest. Coding discrepancies highlight the importance of refining coding to capture the complexities of childhood obesity interventions, which often engage multiple recipients (e.g., parents and/or children) and address multiple behaviors (e.g., diet, physical activity, screen time).